Pengaruh Pembiayaan Mikro Terhadap Perkembangan Usaha Mikro Kecil Dan Menengah Pada PT. Bank Syariah Indonesia KCP Stabat - Azkiya Ilma Novliza, Sri Wahyuni, Khairani Sakdiah (CV. Pusdikra Mitra Jaya, 2023)
This study aims to influence microfinance on the development of Micro, Small and Medium Enterprises at PT. Bank Syariah Indonesia KCP Stabat. This type of research is quantitative research that emphasizes numerical data (numbers) processed using inferential statistical methods (analyzing the relationship between variables by testing hypotheses). The source of this research data was obtained from questionnaire answers given by research respondents, namely customers of Micro, Small and Medium Enterprises who received Microfinance from PT. Bank Syariah Indonesia KCP Stabat. The results of the study explain that there is a significant influence between Micro Financing the development of Micro, Small and Medium Enterprises at PT. Bank Syariah Indonesia KCP Stabat. This is evidenced from data analysis using a hypothesis test, namely the t test which shows a smaller significance value of 0.05 or (0.000 <0.05) and tcount > ttable (6.491 > 1.98729) so that there is an influence of variable X on variable Y. Microfinance disbursed by PT. Bank Syariah Indonesia KCP Stabat for Micro, Small and Medium Enterprises actors affects the development of Micro, Small and Medium Enterprises by 31.6%, while the remaining 68.4% is influenced by other variables such as inflation, people's purchasing power, human resources, production/operations, finance, marketing, partnerships, infrastructure, regulation, and so on. The coefficient is positive, meaning that there is a positive or parallel relationship between Microfinance and the Development of Micro, Small and Medium Enterprises, the greater the Microfinance of PT. Bank Syariah Indonesia KCP Stabat is channeled so that the Development of Micro, Small and Medium Enterprises will increase, and vice versa.